The determination of viscosity in barley and using possibilities of barleys, having different viscosity, supplemented with enzyme in layer diets - INAL, F; COSKUN, B; BALEVI, T; UMUCALILAR, H D; GULSEN, N; OZKARA, R (The Indian Journal of Animal Sciences, 2014)
This study was conducted as 3 step set of experiments to investigate the Possibility of using hydrolytic enzyme in laying diets. In the first trial, the crude nutrients and acid extract viscosity values of 78 barley grain samples collected from different regions of Turkiye were determined. CP values were ranging from 9.83 to 13.40% and acid extract vIscosity were from 1.64 to 12.64 cS. Samples were grouped as low, medium and high viscosity barley grains. In the second trial. a commercial enzyme mixture (xylanase, alpha amylase, cellulase, glucanase, pectinase 22%, lactose 75%, citric acid 2.5%, and protease 0.5%) was added to barley samples in an inclusion of 150 mg/kg. Enzyme supply reduced the viscosities like 3.95 to 3.81 for low, 6.14 to 4.20 for medium and 10.07 to 8.53 for high viscosity classed barley samples. A control diet based corn and six experimental diets containing 30% barley (w/w) in low medium and high viscosity subgroups with and without enzyme supplementation were prepared and fed to 2 10 laying hens located in cages at the age of 30 weeks(n=30) for 12 weeks. The productive performance differences between treatment groups were not statistically Significant. Feed consumed per dozen eggs was 2.00kg in control and 2.07kg in high viscosity barley consuming groups. In the third trial, metabolisab Ie energy values of barley samples and the effect of enzyme supplementation on ME were determined in cockerels. The ME values were 13.90, 14:24 and 13.71 MJ/kg DM.